Fifty shades of grace: the crafting of sexual wisdom - Grosch-Miller, Carla A. (Theology & sexuality, 2014)
Each of us has lived sexual experience that gives us embodied knowledge. This embodied knowledge is a primary source for the creation of practical sexual wisdom. We learn by doing, bumping up against others and mining the consequences to create a personal ethic. Grace accompanies us along the way. In this article a model of sexual-spiritual integration is proposed in which embodied knowledge is in critical-liminal conversation with other sources of knowledge to create practical sexual wisdom in a poetic and phronetic process. Such integration is an example of the moral creativity of the human being and derives from the function of sexuality in the person, the story-telling tendency of the brain to create identity, and the narrative intelligibility of human life. Implications for theological education (providing safe space, information, and invitations to critical and liminal reflection) are briefly discussed before particular graces (desire, vulnerability, honesty and wrestling) are explored and illustrated by stories and poems.